Causes and geochemical significance of total organic carbon anomaly in solid residue samples from source rock pyrolysis simulation experiments in a closed system - Hui CANG; Zhijun CHEN; Dong YANG; Yiguo CHEN; Changchun HAN; Ziliang LI; Lingling CHEN (Shiyou shiyan dizhi)
Under natural evolution, the total organic carbon (TOC) content of source rocks typically decreases as maturity increases. However, in later stages of pyrolysis simulation experiments conducted in a closed system, the TOC content of solid residue samples would anomalously increase instead of decreasing. By analyzing data from pyrolysis simulation experiments on lacustrine source rock samples from the Mesozoic Yingen-Ejinaqi Basin, the causes of this TOC content anomaly were investigated, and its geochemical significance was explored. The results suggested that this anomaly was related to secondary cracking of crude oil. In the closed system of the experiments, early-formed crude oil was trapped in the reactor, unable to be discharged. As the temperature increased, large-scale oil cracking occurred, converting it into gaseous hydrocarbons and generating pyrobitumen. The insoluble pyrobitumen adhered to the solid residue samples, resulting in an increase of TOC content. Based on TOC variation curve of solid residue samples from the pyrolysis simulation experiments, a new method was established to determine the main gas generation threshold for oil cracking in different types of source rocks. The significant amount of pyrobitumen generated, accompanied by an increase in TOC content, indicated the onset of large-scale oil cracking and gas generation. This method overcomes the shortcomings of existing methods, such as inevitable human errors in determining the main gas generation threshold and the inability to conduct more in-depth study on mixed-source oils.